2008
DOI: 10.1128/jcm.01943-07
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Extended-Spectrum β-Lactamases among Escherichia coli Isolates Collected in a Swedish Hospital and Its Associated Health Care Facilities from 2001 to 2006

Abstract: The genetic characteristics and molecular epidemiology of extended-spectrum ␤-lactamases (ESBLs) among Escherichia coli isolates were investigated at a general hospital and its associated health care facilities in Stockholm, Sweden, during the period from 2001 to 2006. Of 87 consecutive nonduplicate ESBL-positive isolates, 80 isolates encoded CTX-M-type ESBLs, 64 of which were group 1 enzymes. TEM-type and OXA-type ␤-lactamases were encoded in 63 and 59% of the ESBL isolates, respectively. Pulsed-field gel ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
119
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 23 publications
9
119
1
Order By: Relevance
“…The frequency of the bla CTX-M gene was 90.4% (104/115). Other researchers also reported high prevalence rates of 92% 33 , 82% 14 , 72% 34 and 70% 10 . The frequency of the bla TEM was 75% (86/115), which resembles the results of the studies conducted in Sweden and Brazil 10,33 .…”
Section: Discussionmentioning
confidence: 89%
“…The frequency of the bla CTX-M gene was 90.4% (104/115). Other researchers also reported high prevalence rates of 92% 33 , 82% 14 , 72% 34 and 70% 10 . The frequency of the bla TEM was 75% (86/115), which resembles the results of the studies conducted in Sweden and Brazil 10,33 .…”
Section: Discussionmentioning
confidence: 89%
“…Plasmids are major mechanism for the spread of antibiotic resistant genes in bacterial populations [9]. Conjugation occurs by F-plasmids that can transfer genes encoded for multiple resistance and mobilize other non-conjugative plasmids to host cells.…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, Emilio David Valverde revealed that 30% of E.coli samples taken from 11272 patients of Salamanca Hospital produced ESBLs, which TEM family was 22.1% [18]. However, recent literature increased levels of ESBLs throughout the world.…”
Section: Discussionmentioning
confidence: 99%